Sources of Labor Growth in Malaysian Manufacturing Sector - Tin, Poo Bee; Rashid, Zakariah Abdul (Gadjah Mada International Journal of Business, 2010)
The manufacturing sector plays an important role in Malaysianindustrial development. High growth rates and technology expan-sion in the manufacturing sector resulted in a substantial increasein demand for labor. This process of rapid growth and changes in thedemand for labor were also accompanied by changes in laborstructure and skills. At the same time, the range of activities andproducts became more diversified and, correspondingly the compo-sition of manpower sub sectors changed significantly. This studyemployed the input-output Structural Decomposition Analysis (SDA).The analysis computed the compositional manpower change as aresult of decomposition. The result of this study indicates thatsources of labor growth in the manufacturing sector were favored bychanges in the final demand structure. Within the changes in thefinal demand structure, changes in domestic demand structure werethe dominant source of employment growth between 1978 and 1991and the overall period 1978-2000. However, from 1991 to 2000,employment change was due mainly to changes in export structure.Changes in the structure of domestic demand had a relatively strongand increasing effect on service workers, production and relatedworkers, transport equipment operators, laborers, and clerical andrelated workers during the 1978-1991 period. Changes in the exportstructure were the main factor that had an increasing effect on theÂ employment of high skill workers and sales workers. However,during the second sub period of 1991-2000, manpower growth wasexports structure driven.Keywords: input-output; labor; manufacturing; structural decomposition analysis